CSE1L participates in regulating cell mitosis in human seminoma. (28th November 2018) - Liu, Chunyan; Wei, Jiajing; Xu, Kang; Sun, Xiaosong; Zhang, Huiping; Xiong, Chengliang
Abstract: Objectives: CSE1L has been reported to be highly expressed in various tumours. Testicular germ cell tumours are common among young males, and seminoma is the major type. However, whether CSE1L has functions in the seminoma is unclear. Materials and methods: The expression of CSE1L was detected by immunohistochemistry in seminoma tissues and non‐tumour normal testis tissues from patients. CSE1L distribution during cell mitosis was determined by immunofluorescent staining with CSE1L, α‐tubulin and γ‐tubulin antibodies. The effects of Cse1L knockdown on cell proliferation and cell cycle progression were determined by Cell Counting Kit‐8 assay, flow cytometry, PH3 staining and bromodeoxyuridine incorporation assay. Results: CSE1L was significantly enriched in the seminoma tissue compared with the non‐tumour normal testis tissue. CSE1L also co‐localized with α‐tubulin in the cells with a potential to divide. In the seminoma cell line TCam‐2, CSE1L was associated with the spindles and the centrosomes during cell division. The knockdown of CSE1L in TCam‐2 cells attenuated the cells' proliferative capacity. Cell cycle assay revealed that the CSE1L‐deficient cells were mainly arrested in the G0/G1 phase and moderately delayed in the G2/M phase. The proportion of cells with multipolar spindle and abnormal spindle geometry was obviously increased by CSE1L expression silencing in the TCam‐2 cells. Conclusions: Overall, these findings showed that CSE1L plays a pivotal role in maintaining cell proliferation and cell division in seminomas.